HUBUNGAN KEDISIPLINAN DOSEN TERHADAP MOTIVASI DAN PARTISIPASI BELAJAR MAHASISWA PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM - Saepulmilah, Ceceng; Azhari, Septian Cahya (JURNAL AL-QAYYIMAH, 2022)
This study aims to determine the relationship between lecturer discipline on motivation and student participation in online learning. The method used in this study is a quantitative approach with data analysis techniques, path analysis, structural equation modeling (SEM-PLS). The population in this study were students of the Civil Engineering study program at the University of Siliwangi which was then taken as many as 100 samples by proportional random sampling. The results showed that the original sample value of discipline on motivation was 440 and P values of 0.000, the value of the original sample of discipline on learning participation was 423 and p-values of 0.000. So it can be concluded that there is a significant relationship between lecturer discipline on motivation and student learning participation in online learning.